Alkali activated persulfate mediated extracellular organic release on enzyme secreting bacterial pretreatment for efficient hydrogen production. (December 2021) - Preethi; Rajesh Banu, J.; Godvin Sharmila, V.; Kavitha, S.; Varjani, Sunita; Kumar, Gopalakrishnan; Gunasekaran, M.
Graphical abstract: Highlights: Fermentative production of biohydrogen from waste activated sludge. SPS disrupts the flocs in sludge and thereby hydrogen production increases. Enzyme secreting bacterial pretreatment increases the soluble organics. Hydrogen production of 103.8 mL/gCOD obtained from SPS-BP sludge. Efficient process with net energy of 0.01 kWh per ton of sludge. Abstract: The present investigation is proposed to assess the competency of Sodium Persulphate (SPS) induced enzyme secreting bacterial pretreatment in enhancing the generation of biohydrogen from waste activated sludge (WAS). Alkali activated SPS of dosage 0.015 g/g SS has been opted to disseminate the floc structure to fortify the release of Extracellular polymeric substance (EPS) into aqueous phase. This removal of EPS enhances the bacterial disintegration fostering 18.71% of suspended solids reduction and 21% of COD solubilization which was comparatively higher than bacterially pretreated (BP) and control (C) sludge. Biohydrogen production of control (C), bacterially pretreated (BP) and SPS mediated bacterially pretreated (SPS-BP) sludge were found to be 32.2 mLH2 /g COD, 48.3 mLH2 /g COD and 103.8 mLH2 /g COD respectively. The net energy production of SPS - BP is 0.01 kWh which is higher than the C and BP sample during the entire treatment and obtained energy ratio greater than 1.